2018
DOI: 10.18203/2319-2003.ijbcp20181655
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and perception about generic drugs in patients coming to OPD of tertiary care centre

Abstract: Background:In an era of rapidly rising health care costs generic medicines provide a less expensive alternative to branded medicines. In addition to reducing the overall health care expenditure, it has been shown to improve adherence. Objective was to study knowledge and perception about generic drugs among patients coming to outpatient department of tertiary care centre. Methods: After ethical approval a cross sectional questionnaire based study was conducted. Patients (n=71) were interviewed according to que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…reported similar results where 35.21% of patients had a good awareness of the generic drugs. [ 12 ] Studies by Tripathi and Bhattacharya in northern India reported that 72% and Jangra et al . reported 92% of participants were aware or heard about generic medicines which were quite higher as compared to our study but the sample size of these studies were relatively lesser than our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…reported similar results where 35.21% of patients had a good awareness of the generic drugs. [ 12 ] Studies by Tripathi and Bhattacharya in northern India reported that 72% and Jangra et al . reported 92% of participants were aware or heard about generic medicines which were quite higher as compared to our study but the sample size of these studies were relatively lesser than our study.…”
Section: Discussionmentioning
confidence: 99%
“…(18.31%). [ 12 ] The probable reason behind low use could be the decision of prescription being taken by physicians and patients have a restricted role in deciding the type of medication. This study also reported that 78.6% of patients do not trust generic medicines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interns where students (94.5%) and interns (74%) were aware of the concept of generic drugs. 22 Students were usually taught about generic drugs in 2nd year MBBS Pharmacology class; but they gradually tend to forget by the time they start internship. In the present study only 43 (33.1%) of students and 47 (70.1%) of interns know that generic medicines are available only at Pradhanamantri Bharathiya Jan Aushadhi Kendra.…”
Section: Medical Studentsmentioning
confidence: 99%